(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
Supplementary Cementitious Materials (SCMs) have become essential in the development of high-strength and high-performance concrete. These materials include naturally occurring pozzolans, industrial by-products, and low-energy materials that contribute to sustainable construction practices. This study examines the impact of incorporating thermally activated Iraqi metakaolin (MK) produced by calcining kaolinite clay at 600°C for 3 hours as a partial replacement for Ordinary Portland Cement (OPC) in mortars and concretes. The metakaolin cools rapidly to preserve its amorphous and reactive structure. Replacement ratios of 10%, 15%, 20%, and 25% by weight of cement are tested and compared with a control mix containing no MK. A comprehensive set of physical and chemical tests, including Blaine fineness, setting times, compressive strength, and chemical composition. The results indicate a notable enhancement in the mechanical and durability properties, especially at 10% replacement, which demonstrates optimal performance. Beyond technical improvements, the use of metakaolin also offers environmental advantages such as reduced clinker content, lower CO₂ emissions, and the utilization of abundant local resources. These findings position the Iraqi metakaolin as a promising SCM that aligns with global trends in green and sustainable construction, making it a practical and eco-friendly solution for modern cement-based systems.